2020
DOI: 10.46244/geej.v7i2.1180
|View full text |Cite
|
Sign up to set email alerts
|

English Teaching Materials During Global Pandemic: A Survey on Online Learning at Vocational Schools in Lampung

Abstract: Coronavirus spread around the world affects many things. Education is one of many affected sectors. Indonesia is a country which mostly effected by Coronavirus. Thousand students throughout the nations left the schools and start adapting a distance learning. It forces all teachers and students to learn and adapt to online learning. English teaching materials play a role in providing students with contextual knowledge. By far, English learning materials have only been inserted about moral values and other value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Furthermore, some studies were related to online classes in teaching media. Algiovan and Roza (2020) found that most English teachers in vocational schools in Lampung used WhatsApp to deliver material in online classes. Sari and Putri (2022) stated various teaching media in Yogyakarta, including chat and messages, assessment tools, video conferencing, learning management systems, content makers, video learning, and sharing platforms.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, some studies were related to online classes in teaching media. Algiovan and Roza (2020) found that most English teachers in vocational schools in Lampung used WhatsApp to deliver material in online classes. Sari and Putri (2022) stated various teaching media in Yogyakarta, including chat and messages, assessment tools, video conferencing, learning management systems, content makers, video learning, and sharing platforms.…”
Section: Introductionmentioning
confidence: 99%
“…The distance learning process for vocational education is also carried out by Purnamasari (2021), Mahmut (2020), Syauqi, Munadi, and Triyono (2020), and Edy (2020) by identifying the steps taken in online learning and compared to the conventional learning process. To find out the materials and platforms used during distance learning in vocational education, research has been conducted by Algiovan and Roza (2020), Edy (2020), Syauqi, Munadi, and Triyono (2020), Aydin et al (2015), Mukarromah and Wijayanti (2021), and provided suggestions related to the learning process by improving disaster education at all levels. A comprehensive analysis is also carried out to find the most influencing factors toward online learning during the Covid-19 pandemic (Alqahtani & Rajkhan, 2020).…”
Section: Introductionmentioning
confidence: 99%